TCP-NewReno Protocol Modification for MANET Networks; Communications in Computer and Information Science; Vol. 638 : Information Technologies and Mathematical Modelling - Queueing Theory and Applications, ITMM 2016 - Iovlev D. I. Denis Igorevich (2014, 2014)
Title screen